A tri-serine tri-lactone scaffold for the quantification of citrate in urine. Issue 9 (15th December 2015) - Akdeniz, Ali; Caglayan, Mehmet Gokhan; Anzenbacher, Pavel
Abstract : Tri-serine tri-lactone based fluorescent sensors can discriminate structurally similar anions, including mono-, di- and tri-carboxylates with 100% correct classification. Abstract : Tri-serine tri-lactone based C 3 symmetry fluorescent sensors were synthesized. Citrate is shown to bind to sensors, while displaying an increase in fluorescence intensity for the sensor with thiourea and a quenching for the sensor with sulfonamide. Information-rich responses of the sensors enable us to discriminate structurally similar anions, including mono-, di- and tri-carboxylates with 100% correct classification. A simple two-sensor array enables the determination of the concentration of citrate in urine without any sample preparation with high accuracy (error < 2%).